Maxillary Incisive Canal Characteristics: A Radiographic Study Using Cone Beam Computerized Tomography - Penala Soumya; Pradeep Koppolu; Krishnajaneya Reddy Pathakota; Vani Chappidi (Radiology Research and Practice)
Background. The incisive canal located at the midline, posterior to the central incisor, is an important anatomic structure of this area to be considered while planning for immediate implant placement in maxillary central incisor region. The purpose of the present study is to assess incisive canal characteristics using CBCT sections. Materials and Methods. CBCT scans of 79 systemically healthy patients, with intact maxillary incisors, were evaluated by two calibrated and independent examiners. Assessments included (1) mesiodistal diameter, (2) labiopalatal diameter, (3) length of the incisive canal, (4) shape of incisive canal, and (5) width of the bone anterior to the incisive foramen. Results. The mean width of the foramen labiopalatally and mesiodistally was 3.12 ± 0.94 mm and 3.23 ± 0.98 mm, respectively. Mean canal length was 18.63 ± 2.35 mm and males have significantly longer incisive canal than females. The mean width of bone anterior to the incisive canal was 6.32 ± 1.43 mm. As age of the subjects increased, incisive foramen diameter and incisive canal length were found to be increased. Cylindrical shaped incisive canals were seen in most of the individuals followed by funnel shaped and hour-glass shaped canals, and banana-like canal is least prevalent type. Conclusion. The findings from the present study suggest that the diameter and length of incisive canal vary among different individuals and presence of very thin bone anterior to the canal would suggest that a pretreatment CBCT scan is a valuable tool to evaluate anatomic variations, morphology, and dimensions of incisive foramen before immediate implant placement in maxillary central incisor region.